PERAN RELIGIUSITAS DALAM PENYUSUNAN LAPORAN KEUANGAN DI PT. JANUS GLOBAL TRADE KAB. BONE - Kirana, Ayu Puspa; Fitri, Nur Aulia; Hasminiar, Hasminiar; Marzuki, Sitti Nikmah; Rahmayanti, Vera (Politeknik Bisnis Indonesia, 2024)
In general, financial statements are prepared by business entities to provide an overview of their financial performance to related parties such as owners, investors, employees, creditors, and others. This is in line with the function of financial statements according to Statement of Financial Accounting Concept (SFAC) Number 1, which is to provide data or information that is useful for potential shareholders and other users of financial statements to assist them in making economic decisions, based on cases of accounting fraud and misuse of financial statements, researchers are interested in examining the role of moral ethics in the aspect of religiosity in making financial statements, while the research method used is field research with qualitative descriptive data analysis. Based on the research results, the preparation of the company's financial statements is made within a certain period, this period depends on the policies of each company. Especially at PT Janus Global Trade, the preparation of financial statements is carried out simply every month. But it cannot be denied, of course there are obstacles faced by the compiler of financial statements that can indirectly cause errors in the preparation of financial statements, such as missing or late deposit of proof of transactions to the finance division, discrepancies with other related divisions, and late payment of receivables that exceed the specified period.